Sugar-based surfactants with amide linkage / Salih Mahdi Salman - Salman, Salih Mahdi (2013)
The first part deals with the synthesis and characterization of new sugar amide based surfactants from renewable materials via Staudinger reaction. The starting materials are carbohydrates (e.g. glucose and lactose) and fatty acid derivatives based on both straight and branched carboxylic acids with a total chain length of C8 to C16. Target applications of the surfactants focus on the stabilization or emulsions, in particular water-in-oil emulsions, as well as on life-science, e.g. drug delivery. The second part of the research deals with the study of the physical and chemical properties of the synthesized surfactants, especially with respect to phase and assembly behavior, focusing on potential applications as emulsifying agents. Three series of surfactant were synthesized from various starting materials, i.e. methyl glucoside as well as glucose and lactose based diazides. The synthetic scheme applied a multi-step methodology, including protection, activation, functionalization, Staudinger based coupling with fatty acids and finally deprotection of the surfactants. The characterization, of the surfactants used 1H and 13C NMR, IR, combustion analysis as well as high resolution mass spectroscopy. Physical properties were studied by optical polarizing microscopy (OPM), differential scanning calorimetry (DSC) and surface tension measurements. Lyotropic phases were investigated by contact penetration with water and oil under the OPM, while surface tension measurements used the DuNouy ring approach. The latter enables the determination of critical micelle concentrations.